Peran Dining Experience Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Di Restoran Mywarung Pererenan - Ida Bagus Maha Putra; Made Artajaya; I Gusti Agung Febrianto (JURNAL GASTRONOMI INDONESIA, 2023)
This study aims to the effect of dining experience on customer loyalty, examine the effect of dining experience on customer satisfaction, the effect of customer satisfaction on customer loyalty, and  the effect of customer satisfaction. dining experience on customer loyalty with customer satisfaction. as a mediating variable. Data collection using the questionnaire method. The population in this study were customers who had visited, ate and had a customer loyalty card at the MyWarung Pererenan restaurant by walk-in in 2020 as many as 12,639 people. The technique used in this research is purposive sampling which aims to determine the sample with the criteria of customers who have visited and dined and provide a positive online review at the MyWarung Pererenan restaurant. The number of samples is 100 people and all of them provide answers. The analytical technique used Sobel test. The results showed that the dining experience had a positive and significant effect on customer loyalty, the dining experience had a positive and significant effect on customer satisfaction, customer satisfaction had a positive and significant effect on customer loyalty, and customer satisfaction had a positive and significant effect on customer satisfaction. mediation on the relationship between dining experience and customer loyalty.